FROM SUBJUGATION TO SELF-REALIZATION: ANALYSING THE TENSION BETWEEN POWER AND IDENTITY IN THE CASTLE BY HOWARD BARKER - Sibgatuullah Nazki; Jammu; Kashmir (Adisam Publisher, 2025)
Howard Barker’s The Castle explores power, identity, and self-realization in a post- crusade medieval society. Barker’s Theatre of Catastrophe rejects conventional narratives, focusing on ambiguity and moral paradox. The play examines the clash between patriarchal authority, personal desires, and the communal upheaval caused by returning crusaders. This study places Barker’s work within critiques of power and explores the conflict between subjugation and agency. This paper examines how Barker depicts the interplay of power and identity in the play. It focuses on characters transforming under oppressive systems. The study also explores Barker’s critique of dominant ideologies. Using close reading, this study analyses dialogues, characters, and structure in the play. It investigates the treatment of power and identity. The analysis uses poststructuralist theory, particularly Michel Foucault and Judith Butler, to explore identity construction and deconstruction. Barker’s essays and critical analyses of the Theatre of Catastrophe provide additional context. The analysis finds that The Castle portrays power as a dynamic and oppressive force. This force both shapes and fractures identity. Characters like Ann, Skinner, and Stucley resist imposed social, religious, and political roles. Through rebellion and defiance, they assert their agency. Barker’s fragmented narrative and morally ambiguous characters show identity as unstable and contingent. Barker’s The Castle critiques power’s corrosive effects on identity. It also highlights resistance and transformation as paths to self-realization. The play’s unresolved nature reflects the enduring complexity of power relations. By challenging traditional views of authority, Barker invites reflection on complicity in oppressive systems. This study contributes to broader discussions of power and identity in drama and literature. It underscores Barker’s relevance to political and philosophical debates.